(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
This study was conducted with the objective of determining theeffect of application of different irrigation water amounts on the yield ofwheat grown on different seedbeds. Three irrigation water regimesnamely: 100%, 80% and 60% of crop evapotranspiration (Etc) were usedunder two types of seedbeds (sowing on the flat and sowing on ridges)over two successive seasons (2003/04–2004/05) at the DemonstrationFarm of the Faculty of Agriculture, University of Khartoum, Shambatusing a strip-split-plot design with three replications. The control was flatsown and with no-tillage. Data were collected to determine variablespertaining to plant population, plant height, number of tillers, leaf areaindex (LAI), number of spikelets/plant and grains/spike, 1000-grainsweight, harvest index (HI), total grain yield and water use efficiency(WUE). Results obtained revealed that, the watering regime of 60% ETcwas statistically inferior in almost all the mentioned parameters, and thatthe 100% and 80% ETc had similar results in both seasons.